HARGA BATUBARA DAN INDEKS HARGA SAHAM GABUNGAN TERHADAP RETURN SAHAM PERUSAHAAN PERTAMBANGAN - Sumani .; Panca Wiputra; Christine Winstinindah S. (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2012)
Coal is the largest fossil energy sources and according to the basic scenario of primary energy supply mix in 2025 consisted of coal 33%, followed by gas (30%), petroleum (20%), and renewable energy (17%). Indonesia has a lot of potential in the natural resources of coal mining, so many investors conduct investment activities in the coal mining sector, one way is with a stock investment instruments. We want to examine the effect of coal prices and the Composite Stock Price Index which represented the market influence on stock returns of coal mining companies. Determination of the sample in this study using a non probability sampling with a purposive sampling technique, companies that meet the criteria are companies that have made the public stock offering before the year 2008. Data were analyzed using multiple regression methods. The study results showed that coal prices do not provide a significant positive effect on stock returns of coal mining companies. Composite Stock Price Index provides significant and positive influence on stock returns of coal mining companies. Simultaneously two independent variables (coal prices and stock price index) have a significant influence on the dependent variable (stock returns coal mining company). The results are consistent with the theory of leading indicators, traditional stock valuation theory and the theory of Wealth Effect.